Réponses

2013-12-17T12:46:42+01:00
Bonjour
5 ( 1/2 + 3/4) = 5( (1*2)/(2*2) + 3/4 ) = 5 * 5/4 = 25/4 
2/3+(4/3)6 = 2/3 + 24/3 = 26/3 
13/12 - (3/2)(1/3) = 13/12 - ((3*1) /(2*3)) = 13/12 - 3/6 = 13/12 - 6/12 = 7/12
7/2 ( 3/5+1/10) = 7/2 ( 6/10+1/10) = 49/20 
7/8 + 24(5/16) = 7/8 + 120/16 = 7/8 + 60/8 = 67/8 

2013-12-17T13:00:26+01:00
1)5x (1sur2 + 3sur4) = 5 ( 1/2 + 3/4) = 25/4 = 6+1/4
                
2)7sur2 x ( 3sur5+ 1sur10) = 7/2 ( 3/5+1/10) = 7/2 ( 6/10+1/10) = 49/20 = 2+9/20

3)2sur3+4sur3 x 6 = 2/3+(4/3)6 = 2/3 + 24/3 = 26/3 = 8 + 2/3
                     
4)7sur8+ 24 x 5sur16 = 7/8 + 24(5/16) = 7/8 + 120/16 = 134/16 = 67/8 = 8+3/8

5)13sur12- 3sur2 x 1sur3 = 13/12 - (3/2*1/3) = 13/12 - 3/6 =  13/12 - 6/12 = 7/12